THE EFFECTS OF EXCHANGE RATE AND INFLATION TOWARD TAX REVENUE - Mulyati, Yati (International Journal of Psychosocial Rehabilitation, 2020)
Tax as a function of budget always tries to increase tax revenue to run the life wheel of a country. Many factors can influence increasing tax revenue. This research was conducted to find out how much influence, partially, the exchange rate and inflation factors that occur in increasing tax revenue. The data used in this study are time series data sourced from the Central Statistics Agency and the Ministry of Finance. The saturated sample is the method used in sample selection so that the entire sample is used during the observation period: 2 samples were selected; as many as 60 samples were collected and analyzed using multiple regression analysis. Inflation affects tax revenue.